Evaluation and Improvement of Thermal Comfort and Indoor Air Quality in Post-Disaster Permanent Housing: A Case Study of Bingöl, Türkiye (International Journal of Built Environment and Sustainability, 2025)
Post-disaster permanent housing plays a critical role in long-term recovery. In cold-climate regions like Bingöl, Türkiye, such housing must ensure adequate thermal comfort and indoor air quality (IAQ) to support occupant well-being. This study evaluates the environmental performance of a representative single-storey post-earthquake housing unit constructed after the 2003 Bingöl earthquake. Field measurements were conducted between December 2023 and February 2024 in five rooms, recording temperature, relative humidity, air velocity, CO² concentrations and PM (PM₁–₁₀) levels. Results revealed that most rooms failed to meet ASHRAE 55 winter comfort thresholds, with temperature deviations exceeding 3.5°C in under-heated spaces. Stoves improved thermal comfort but elevated CO₂ and PM concentrations, indicating trade-offs between comfort and IAQ. Dynamic simulations using DesignBuilder tested envelope retrofit scenarios including insulation and glazing upgrades. Simulations showed a 7.1% reduction in discomfort hours, 60% lower heating energy demand, and a 12.3% drop in CO₂ emissions. These improvements were cost-effective and readily applicable in post-disaster contexts. This study contributes by combining field-based environmental data with simulation modelling to assess both thermal comfort and IAQ in cold-climate post-disaster housing. The findings inform resilient and sustainable housing strategies for future disaster recovery efforts.
Keywords: Department of Architecture, Bingöl University, Selahaddin-i Eyyubi, Üniversite Caddesi No:1, 12000 Merkez/Bingöl, Türkiye.